Crystal structure of 4-chloro-N′-[(1E)-pyridin-3-ylmethylidene]benzohydrazide, C13H10ClN3O - Al-Wahaibi, Lamya H.; Blacque, Olivier; Tiekink, Edward R. T. *; El-Emam, Ali A. (De Gruyter, 2023)
C13H10ClN3O, monoclinic, P21/c (no. 14), a = 19.0933(2) Å, b = 23.0910(3) Å, c = 10.6831(2) Å, β = 90.064(1)°, V = 4710.00(12) Å3 , Z = 16, Rgt(F) = 0.0411, wRref(F2 ) = 0.1081, T = 160 K. CCDC no.: 2233777